Paradigma Maqasid Fiqih dalam Dakwah Kampus di Tengah Masyarakat Multikultural - Siswanto, Eko; Islamy, Athoillah (Fahima, 2025)
This qualitative study with a case study approach aims to identify the dimensions of maqasid sharia values in the role of da'wah of the academic community of the Fattahul Muluk Papua State Islamic Institute in a multicultural society. The contemporary maqasid sharia theory conceptualized by Jasser Auda becomes the theory of analysis. Data collection uses observation, interview, and documentation techniques. This study confirms the dimensions of maqasid sharia values in the paradigm of da'wah by the academic community of the Fattahul Muluk Papua State Islamic Institute in building religious harmony in a multicultural society, including the value of hifz ‘irdh in disseminating tolerance and anti-radicalism through the activities of majelis taklim, community organisations, and scientific research publications. Then, the value of hifz waton in disseminating attitudes of national commitment through cooperation programmes between government agencies in strengthening nationalism. Third, the value of hifz ummah in the dissemination of an accommodating attitude towards culture through cooperation programs between government institutions in preserving local cultural wisdom. The findings of this study confirm the expansion of the dimensions of maqasid sharia values can be a paradigm of fiqh da'wah in the midst of multicultural society.